Density Functional Theory Study of Electronic Structures in Lithium Silicates: $Li_2SiO_3$ and $Li_4SiO_4$ (Journal of Atomic and Molecular Sciences, 2010)
Lithium silicates, such as $Li_2SiO_3$ and $Li_4SiO_4$, are consideredas favorable candidates for the tritium breedingmaterials of a nuclear fusion reactor. Their bulk electronicproperties and mechanics are important for the tritium behavior andtritium breeding blanket designs. We have studied the structural and electronic properties of $Li_2SiO_3$ and $Li_4SiO_4$ bulks using density functionaltheory (DFT) within generalized gradient approximation(GGA). Thecalculated crystal parameters are well consistent with the experimental results. The electronic band energy calculations showthat $Li_2SiO_3$ and $Li_4SiO_4$ are insulators with a band gapof about 5.36 and 5.53 eV, respectively. Their valence bandproperties are mainly determined by the oxygen 2$p$ orbital electrons.The two types of oxygen atoms, nonbridging oxygen (NBO) atoms andbridging oxygen (BO) atoms, in $Li_2SiO_3$ reveal significantlydifferent electron distribution of oxygen 2$p$ orbital. The Si 3$s$ and3$p$ hybridization is observed in $Li_2SiO_3$, but not in $Li_4SiO_4$. In both lithium silicates, the electronic densityincreases more steeply around $Li$ and $Si$ atom sites compared withthat around $O$ atoms. Additionally, the mechanical properties of both lithium silicates were calculated and discussed first time.